Cigarette smoking associated with chronic pancreatitis: a case control study in China - Lai, Yamin; Yang, Hong; Han, Wei; Guo, Tao; Lv, Hong; Li, Jingnan; Qian, Jia-Ming (Tobacco induced diseases, 2017)
Background: Chronic pancreatitis (CP) is a long-term inflammatory disease affecting the pancreas. No studies are currently available associating cigarette smoking with CP in Chinese mainland population. This study aims to assess the evidence for tobacco smoking as a risk factor for CP and to find the dose-response relationship between them precisely in Chinese mainland population. Methods: This retrospective study enrolled Chinese patients with CP and control patients at the Peking Union Medical College Hospital from 1983 to 2008. Demographic and clinical data were collected, and Chi-square (χ2) test and a Cox proportional hazards regression model were used for statistical analysis. This study evaluated whether cigarette smoking is a risk factor for CP in 346 patients and 346 healthy controls (CP group: 267 males, 79 females; control group: 270 males, 76 females) with mean ages of 49 and 49.2 years, respectively. Results: In the CP group, 46.8% were smokers, and 41% were drinkers. Heavy smokers (≥ 20 cigarettes/d), who were either male (P = 0.03) or older than 30 years (P = 0.045), or males older than 30 years (P = 0.021), were significantly more prone to CP than light smokers. CP patients, regardless of their gender, who had smoked for more than 30 years and were without biliary disease had a significantly higher risk to develop CP compared with health control group (OR = 2.35, 95% CI: 1.106 – 4.973, P = 0.026). There was no statistically significant association between smoking duration of less than 30 years and the risk of CP regardless of gender, age, or biliary disease. Conclusions: Cigarette smoking is an important risk factor for CP in the Chinese population and correlates with risk factors, such as age, gender, biliary disease, and alcohol consumption. In conclusion, cigarette smoking is an important risk factor for CP in the Chinese subpopulation.